Kedudukan Hukum People Power dan Relevansinya dengan Hak Kebebasan Berpendapat di Indonesia - Muhamad Iqbal Susanto (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
This article is here to examine the legal position of People Power which is associated with the constitutional movement considering that interpretations relating to People Power in Indonesia are still very diverse. The writing method used is the deductive method. This article concludes that People Power is synonymous with the spread of propaganda both through social media, demonstrations, and the greater emphasis on resources mobilized. Then People Power if it is related to constitutional rights based on Article 28 of the 1945 Constitution, concerning association and assembly, expressing thoughts verbally and in writing. Of course as long as it is still in the corridor mandated by the 1945 Constitution, the People Power in question is considered constitutional activity. But on the contrary if the people power is outside the corridor of the 1945 Constitution, where the intended People Power is intended to overthrow by force a legitimate government, then it will automatically be considered as an unconstitutional movement.